Clinical and Magnetic Resonance Spectroscopic Imaging Findings in Veterans With Blast Mild Traumatic Brain Injury and Post-Traumatic Stress Disorder - Kontos, Anthony P. (Mil Med, 2017)
OBJECTIVES: To compare magnetic resonance spectroscopic imaging (MRSI) findings from the hippocampal regions of military veterans with blast-related mild traumatic brain injury (blast mTBI) and post-traumatic stress disorder (PTSD) to those with PTSD only; and to examine the relationship of MRSI findings to cognitive and neuromotor impairment. METHODS: 35 military veterans—23 with blast mTBI and PTSD (blast mTBI/PTSD) and 12 with PTSD only participated in the study. Whole plane MRSI data including N-acetyl aspartate (NAA) and choline (Ch) were acquired at 7T for the hippocampus. Concurrent cognitive and neuromotor data were collected using established assessments. General linear models (GLMs) with Bonferroni correction were used to compare the two groups on NAA/Ch ratios across regions of the hippocampus. Spearman’s correlations were used to examine correlations between NAA/Ch and cognitive and neuromotor impairment. RESULTS: The NAA/Ch results for the left hippocampus were lower in the blast mTBI/PTSD group than the PTSD-only group. The blast mTBI/PTSD group also scored worse on the WAIS-IV-vocabulary. Significant correlations between NAA/Ch and neuromotor outcomes—including vestibular impairment—were supported. CONCLUSIONS: Combined MRSI and cognitive and neuromotor data may help inform more objective and accurate diagnoses and effective treatments for patients with blast mTBI and PTSD.